Optimal techno-economic-environmental study of using renewable energy resources for Yanbu city - Alghamdi, Osama A.; Alhussainy, Abdullah Ali; Alghamdi, Sultan; AboRas, Kareem M.; Rawa, Muhyaddin; Abusorrah, Abdullah M.; Alturki, Yusuf A. (Frontiers in Energy Research, 2023)
Since renewable natural resources like wind and solar are more inexpensive as well as environmentally friendly, developing countries would like to move away from using fossil fuels. This paper focuses on a techno-economic-environmental study and provides Yanbu City with renewable energy. This has been carried out by considering an off-grid system or a system connected to the grid. In order to find the best situation from a technical, economic, and environmental perspective to supply the city, fifteen options were taken into account. The photovoltaic (PV) and wind turbines (WT) connected to the grid make up the grid-connected system. The off-grid system is considering the development of a load profile for Yanbu city. In both systems, an energy storage system (ESS) is essential (off-grid and grid-connected). The results show that the 850 MW PV system connected to the grid without ESS is the best option both economically and technically.